Peningkatan Transparansi Keuangan melalui Audit Pengeluaran Kas - Febrian, Yudha Eka; Fitrianingsih, Dwi (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
In the context of entrepreneurship, especially for micro, small and medium enterprises, the implementation of financial transparency is one of the main pillars in the management of accountable and trustworthy UMKM finances. Cash expenditure audits play an important role in increasing this transparency by ensuring that every cash expenditure transaction is recorded accurately, supported by valid documents, and in accordance with applicable procedures and regulations. Through the audit process, auditors evaluate the recording, authorization, and reporting of cash expenditures, and test the effectiveness of internal controls implemented by the organization or company. Cash expenditure audits also help detect and prevent fraud, embezzlement, or misuse of funds, so that all financial activities can be monitored and accounted for openly to interested parties. The implementation of routine and systematic cash expenditure audits has been proven to increase the trust of stakeholders such as micro, small and medium enterprise owners or investors, strengthen accountability, and encourage the creation of better and more transparent financial governance.Referring to the identified business, participants are guided to carry out accounting records, starting from the initial stage of the business, namely the first investment, procurement of production materials, outcomes, income, and other related transactions.